2019
DOI: 10.1111/ijlh.13017
|View full text |Cite
|
Sign up to set email alerts
|

Quality management and accreditation in laboratory hematology: Perspectives from India

Abstract: Quality management (QM), including quality assurance and quality control, was developed in clinical laboratories in North America and Western Europe, but must be implemented worldwide to ensure accurate, reproducible, and clinically useful results. India, a middle income country with a population of over 1.34 billion, has limited budget allotted to health care. As yet accreditation for clinical laboratories is not mandatory, which contributes to challenges in implementing good laboratory practice. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Nonetheless, wireless technologies nowadays play a large role in many ways, including critical value notification and reporting, but only around one-third of responses to our survey indicated the use of these technologies to deliver the notification which is not matching subsequent study. A study in India [ 16 ] suggested that increased usage of wireless technology in laboratories will improve quality metrics including turnaround time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, wireless technologies nowadays play a large role in many ways, including critical value notification and reporting, but only around one-third of responses to our survey indicated the use of these technologies to deliver the notification which is not matching subsequent study. A study in India [ 16 ] suggested that increased usage of wireless technology in laboratories will improve quality metrics including turnaround time.…”
Section: Discussionmentioning
confidence: 99%
“…Around 87% responses indicated knowledge that a comprehensive list existed, which might acknowledge the importance of critical value notification. Reporting critical values according to a written protocol will address quality assurance and avoid tests reference ranges errors [ 16 ]. Medical societies—usually guided by medical professionals representing a particular specialised field—play a role in keeping their community informed about the latest research and developments in that field; following their recommendations aims to ensure that patients receive the best treatment available [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many laboratories are compliant with country‐specific accreditation norms, a few are also compliant with international accreditations and EQAS programmes. However, these cannot be generalised for all labs in the country, and India faces significant challenges on this account 33 . Turnover times vary from days to weeks for outsourced tests and may potentially affect real‐world clinical management of patients.…”
Section: The Perspective From India (Vs Radhakrishnan and M Chandy)mentioning
confidence: 99%
“…However, these cannot be generalised for all labs in the country, and India faces significant challenges on this account. 33 Turnover times vary from days to weeks for outsourced tests and may potentially affect real‐world clinical management of patients. This challenge is identified as a felt need in the country and regional hubs for testing are being mooted by the Government and professional organisations.…”
Section: The Perspective From India (Vs Radhakrishnan and M Chandy)mentioning
confidence: 99%
“…7 This should be verified within the correct time frame and easily interpreted by healthcare workers. 8 Accredited laboratories are associated with good quality testing. Since 2014, reports have indicated that less than 30% of medical laboratories in Africa are accredited by the internationally recognised bodies, meaning that there are fewer laboratories that have achieved international accreditation status.…”
Section: Sanas Is the Only Internationally Recognised Accreditation Body In Southmentioning
confidence: 99%